Analysis of Credit Sales Management and Bad Debt Write-Off Practices: Evidence from an Indonesian Trading Company - Dewi, Siti Ratna Sari; Sulastri, Ratih (Sean Institute, 2026)
This study examines the management of credit sales and the practices used to recognize uncollectible accounts in an Indonesian trading company. The research aims to evaluate the effectiveness of credit approval procedures, billing processes, and the treatment of doubtful receivables in supporting sound financial reporting and risk control. A qualitative case study approach is employed through interviews with 2 finance personnel and analysis of internal documents related to sales transactions, receivables administration, and write-off procedures. The findings indicate that structured credit screening and coordinated roles between sales and accounts receivable units are essential to mitigate default risk. However, the recognition of uncollectible accounts is still dominated by a direct write-off approach, which may reduce the timeliness and prudence of expense recognition. Strengthening credit policy, enhancing collection monitoring, and adopting a more anticipatory allowance-based approach are recommended to improve the reliability of financial information and the sustainability of credit sales operations.